SUATU METODA UNTUK MENENTUKAN SEMUA MINIMUM SPANNING TREE DALAM SUATU GRAF GRAF . - Narwen
Abstract:<align=\"justify\"> There are several known methods for finding a minimum spanning tree from connected weighted graph. Using Kruskal\'s algorithm and independent components of edges equivalent classes, and also determinant of nonsingular sub matrix of incidence matrix of graph, we will be present a method for the determination of all minimum spanning tree from a given connected weighted graph. These method can also be used for the case where we have minimum spanning tree with constraint.<align=\"justify\">